Entrepreneurship : Four ‘N’ Agency Worker / Noreen Sapuan ... [et al.] - Sapuan, Noreen; Ismail, Nurizzatie; Ayub, Noor Ashikin; Mohayat, Nurul Farhana (2008)
Four 'N' Agency Worker Sdn. Bhd. - is a company that provide workers to fulfil the job vacancy especially in industrial sector in Malaysia. For the beginning, our company decide to provide foreign workers from Indonesia only because of the cost are cheaper and Indonesia near to Malaysia. Our company will try our best to provide employees to satisfy our client we believe that this feature will ensure our success.